2013
DOI: 10.1097/hjh.0b013e32835aa351
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure trends and mortality

Abstract: In very old age, both decreasing trend in SBP over the previous 5 years and the current SBP value independently contribute to prediction of all-cause mortality. Therefore, in individual patients, all available preceding SBP measurements should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
1
35
0
3
Order By: Relevance
“…In several of these studies, a sharply attenuated or even inverse association between BP and cardiovascular risk was found in the highest age groups. [28][29][30][31][32] The age at which the association inversed in these studies is not unequivocal, but seems to be in the range of 75 to 85 years. In addition, a J-shaped association of diastolic BP with mortality and myocardial infarction was found in patients with cardiovascular disease, suggesting that excessive reduction of diastolic BP in these patients should be avoided.…”
Section: Risk Of Cardiovascular Events and Mortalitymentioning
confidence: 87%
See 1 more Smart Citation
“…In several of these studies, a sharply attenuated or even inverse association between BP and cardiovascular risk was found in the highest age groups. [28][29][30][31][32] The age at which the association inversed in these studies is not unequivocal, but seems to be in the range of 75 to 85 years. In addition, a J-shaped association of diastolic BP with mortality and myocardial infarction was found in patients with cardiovascular disease, suggesting that excessive reduction of diastolic BP in these patients should be avoided.…”
Section: Risk Of Cardiovascular Events and Mortalitymentioning
confidence: 87%
“…Indeed, the majority of the latter studies explicitly included older persons with high levels of comorbidity, frailty, activities of daily living dependency, or cognitive impairment. [28][29][30][31][32] However, no study has systematically addressed the impact of general health status in the aggregate of the earlier cohort studies in an analysis similar to that performed by the Prospective Studies Collaboration. A second question that must be addressed is whether it would be possible to pinpoint the most appropriate way to assess general health/frailty in this particular context.…”
Section: Risk Of Cardiovascular Events and Mortalitymentioning
confidence: 99%
“…40 In the Leiden 85-plus Study, we previously showed that in the oldest old, declines in blood pressure during followup associate with increased mortality risk. 6,41 A limitation of our study is that information on cardiac output and cerebral perfusion is not available. Echocardiography was only performed in a convenience sample of 90 year olds, and unfortunately not at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, up to about age 70 years systolic blood pressure (SBP) increases continuously with age (23) and high SBP is a well-recognised risk factor for CVD and associated mortality (24)(25)(26) . At higher ages, however, SBP decreases rather than increases with age (23) and higher blood pressure becomes protective in terms of all-cause mortality and cognition, whereas low SBP confers increased risks for mortality, cognitive impairment and disability (17,(27)(28)(29)(30)(31) . Similarly, short peripheral blood telomere length (TL) is recognised as a risk factor for both mortality and (multi-) morbidity (32)(33)(34)(35)(36)(37) .…”
Section: Use Of Birth Cohorts For Biomarker Validationmentioning
confidence: 99%
“…However, the general pattern remained even for participants not on antihypertensive medication and after adjustment for survivor bias (23) . Moreover, low SBP predicted increased mortality in 90-year olds without heart failure, defined by low levels of N-terminal prohormone of brain natriuretic peptide (30,41) . Life history cohorts are the ideal test bed to establish the age dependency of candidate biomarkers of ageing.…”
Section: Use Of Birth Cohorts For Biomarker Validationmentioning
confidence: 99%